Revision of the subfamily Opiinae (Hymenoptera, Braconidae) from Hunan (China), including thirty-six new species and two new genera - Li, Xi-Ying (Pensoft Publishers, 2013)
Abstract. The species of the subfamily Opiinae (Hymenoptera: Braconidae) from Hunan (Oriental China) are revised and illustrated. Thirty-six new species are described: Apodesmia bruniclypealis Li & van Achterberg, sp. n., Apodesmia melliclypealis Li & van Achterberg, sp. n., Areotetes albiferus Li & van Achterberg, sp. n., Areotetes carinuliferus Li & van Achterberg, sp. n., Areotetes striatiferus Li & van Achterberg, sp. n., Coleopioides diversinotum Li & van Achterberg, sp. n., Coleopioides postpectalis Li & van Achterberg, sp. n., Fopius dorsopiferus Li, van Achterberg & Tan, sp. n., Indiopius chenae Li & van Achterberg, sp. n., Opiognathus aulaciferus Li & van Achterberg, sp. n., Opiognathus brevibasalis Li & van Achterberg, sp. n., Opius crenuliferus Li & van Achterberg, sp. n., Opius malarator Li, van Achterberg & Tan, sp. n., Opius monilipalpis Li & van Achterberg, sp. n., Opius pachymerus Li & van Achterberg, sp. n., Opius songi Li & van Achterberg, sp. n., Opius youi Li & van Achterberg, sp. n., Opius zengi Li & van Achterberg, sp. n., Phaedrotoma acuticlypeata Li & van Achterberg, sp. n., Phaedrotoma angiclypeata Li & van Achterberg, sp. n., Phaedrotoma antenervalis Li & van Achterberg, sp. n., Phaedrotoma depressiclypealis Li & van Achterberg, sp. n., Phaedrotoma flavisoma Li & van Achterberg, sp. n., Phaedrotoma nigrisoma Li & van Achterberg, sp. n., Phaedrotoma protuberator Li & van Achterberg, sp. n., Phaedrotoma rugulifera Li & van Achterberg, sp. n., Li & van Achterberg,Phaedrotoma striatinota Li & van Achterberg, sp. n., Phaedrotoma vermiculifera Li & van Achterberg, sp. n., Rhogadopsis latipennis Li & van Achterberg, sp. n., Rhogadopsis longicaudifera Li & van Achterberg, sp. n., Rhogadopsis maculosa Li, van Achterberg & Tan, sp. n., Rhogadopsis obliqua Li & van Achterberg, sp. n., Rhogadopsis sculpturator Li & van Achterberg, sp. n., Utetes longicarinatus Li & van Achterberg, sp. n. and Xynobius notauliferus Li & van Achterberg, sp. n. Areotetes van Achterberg & Li, gen. n. (type species: Areotetes carinuliferus sp. n.) and Coleopioides van Achterberg & Li, gen. n. (type species: Coleopioides postpectalis sp. n. are described. All species are illustrated and keyed. In total 30 species of Opiinae are sequenced and the cladograms are presented. Neopius Gahan, 1917, Opiognathus Fischer, 1972, Opiostomus Fischer, 1972, and Rhogadopsis Brèthes, 1913, are treated as a valid genera based on molecular and morphological differences. Opius vittata Chen & Weng, 2005 (not Opius vittatus Ruschka, 1915), Opius ambiguus Weng & Chen, 2005 (not Wesmael, 1835) and Opius mitis Chen & Weng, 2005 (not Fischer, 1963) are primary homonymsandarerenamed into Phaedrotoma depressa Li & van Achterberg, nom. n., Opius cheni Li & van Achterberg, nom. n. andOpius wengi Li & van Achterberg, nom. n., respectively. Phaedrotoma terga (Chen & Weng, 2005) comb. n.,Diachasmimorpha longicaudata (Ashmead, 1905) and Biosteres pavitita Chen & Weng, 2005, are reported new for Hunan, Opiostomus aureliae (Fischer, 1957) comb. n. is new for China and Hunan; Xynobius maculipennis(Enderlein, 1912) comb. n. is new for Hunan and continental China and Rhogadopsis longuria (Chen & Weng, 2005) comb. n. is new for Hunan. The following new combinations are given: Apodesmia puncta (Weng & Chen, 2005) comb. n., Apodesmia tracta (Weng & Chen, 2005) comb. n., Areotetes laevigatus (Weng & Chen, 2005) comb. n., Phaedrotoma dimidia (Chen & Weng, 2005) comb. n., Phaedrotoma improcera (Weng & Chen, 2005) comb. n., Phaedrotoma amputata (Weng & Chen, 2005) comb. n., Phaedrotoma larga (Weng & Chen, 2005) comb. n., Phaedrotoma osculas (Weng & Chen, 2005) comb. n., Phaedrotoma postuma (Chen & Weng, 2005) comb. n., Phaedrotoma rugulosa (Chen & Weng, 2005) comb. n., Phaedrotoma tabularis (Weng & Chen, 2005) comb. n., Rhogadopsis apii (Chen & Weng, 2005) comb. n., Rhogadopsis dimidia (Chen & Weng, 2005) comb. n., Rhogadopsis diutia (Chen & Weng, 2005) comb. n., Rhogadopsis longuria (Chen & Weng, 2005) comb. n., Rhogadopsis pratellae(Weng & Chen, 2005) comb. n., Rhogadopsis pratensis (Weng & Chen, 2005) comb. n., Rhogadopsis sculpta (Chen & Weng, 2005) comb. n., Rhogadopsis sulcifer (Fischer, 1975) comb. n., Rhogadopsis tabidula(Weng & Chen, 2005) comb. n., Xynobius complexus (Weng & Chen, 2005) comb. n., Xynobius indagatrix (Weng & Chen, 2005) comb. n., Xynobius multiarculatus (Chen & Weng, 2005) comb. n. The following (sub)genera are synonymised: Snoflakopius Fischer, 1972, Jucundopius Fischer, 1984, Opiotenes Fischer, 1998, and Oetztalotenes Fischer, 1998, with Opiostomus Fischer, 1971; Xynobiotenes Fischer, 1998, with Xynobius Foerster, 1862; Allotypus Foerster, 1862, Lemnaphilopius Fischer, 1972, Agnopius Fischer, 1982, and Cryptognathopius Fischer, 1984, with Apodesmia Foerster, 1862; Nosopoea Foerster, 1862, Tolbia Cameron, 1907, Brachycentrus Szépligeti, 1907, Baeocentrum Schulz, 1911, Hexaulax Cameron, 1910, Coeloreuteus Roman, 1910, Neodiospilus Szépligeti, 1911, Euopius Fischer, 1967, Gerius Fischer, 1972, Grimnirus Fischer, 1972, Hoenirus Fischer, 1972, Mimirus Fischer, 1972, Gastrosema Fischer, 1972, Merotrachys Fischer, 1972, Phlebosema Fischer, 1972, Neoephedrus Samanta, Tamili, Saha & Raychaudhuri, 1983, Adontopius Fischer, 1984, Kainopaeopius Fischer, 1986, Millenniopius Fischer, 1996, and Neotropopius Fischer, 1999, with Phaedrotoma Foerster, 1862.